Efektivitas Masase Abdomen terhadap Pencegahan Konstipasi pada Pasien Stroke - Nonika Roma Suryani Sianturi; Dudut Tanjung; Kiking Ritarwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effectiveness of abdominal massage in preventing constipation in stroke patients. The method used is a quasi-experimental two-group pretest-posttest. The sampling technique was conducted by consecutive sampling using the Constipation Assessment Scale (CAS) instrument. The results showed an effect of abdominal massage on the prevention of constipation in stroke patients (p = 0.001) and after the procedure (p = 0.001). In conclusion, abdominal massage is effective in preventing constipation. Keywords: Abdomen, Constipation, Massage, Stroke